Comparison of histological changes of sensory neurons of Dorsal Root Ganglion of spinal nerve in different age groups in rabbits: Ban Ismail Sddiq1, Ali Ghanim Al-Okaili2 and Intisar Jasim3 - Al-Okaili, Ali Ghanim (The Iraqi Journal of Veterinary Medicine, 2015)
The aim of the study is to compare the histological changes that occur in the sensory neurons of dorsal root ganglion at L6 and L7 levels of the spinal nerve in different age groups in rabbits. Fifteen rabbits were divided into three groups of equal number according to their age (weaning, maturation and adult). Dorsal root ganglion of spinal nerve at L6 and L7 levels were removed and examined histologically under light microscope. Comparison were made in diameters of neurons and their numbers in different age. The results showed a significant (P<0.05) decrease in the number of sensory neurons and a significant (P<0.05) increase in their diameters with advancing age. In conclusion, the structures of sensory neurons are altering by the age factors in which morphology, number, and color of neurons change also.